2017
DOI: 10.18632/oncotarget.19051
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, subtypes and associated factors of hyperuricemia in lupus nephritis patients at chronic kidney disease stages 1-3

Abstract: There is a high prevalence of hyperuricemia (HUA) in the chronic kidney disease (CKD) population. However, there’s a dearth of research on HUA’s prevalence, subtypes, early detection, and treatment strategies of HUA in lupus nephritis (LN) patients. The aim of this study is to address these knowledge gaps. LN patients presenting to the Department of Nephrology at Shanghai Rui Jin Hospital from January 2011 to January 2016 were recruited. The effective sample size was derived using the power analysis. The demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 36 publications
(43 reference statements)
0
17
1
7
Order By: Relevance
“…Although intestinal up‐regulation of UA secretion in patients with kidney disease may occur, this compensatory mechanism is likely insufficient, as the prevalence of elevated serum UA levels increases with kidney disease progression, being present in over 90% of individuals with advanced CKD . The possibility of uremic toxin interference with intestinal UA transporters as an explanation for ineffectual intestinal UA excretion has been briefly explored .…”
Section: Causes Of Elevation In Serum Ua Levelsmentioning
confidence: 99%
“…Although intestinal up‐regulation of UA secretion in patients with kidney disease may occur, this compensatory mechanism is likely insufficient, as the prevalence of elevated serum UA levels increases with kidney disease progression, being present in over 90% of individuals with advanced CKD . The possibility of uremic toxin interference with intestinal UA transporters as an explanation for ineffectual intestinal UA excretion has been briefly explored .…”
Section: Causes Of Elevation In Serum Ua Levelsmentioning
confidence: 99%
“…In LN patients with CKD stages prevalence of hyperuricemia in SLE patients is reported to be approximately 16.1% [12] and 29% [13]. In LN patients with CKD stages 1-3, the prevalence of HUA was 40.1% [14]. Despite the fact that hyperuricemia often occurs in SLE patients, the association between LN and hyperuricemia remains insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia is a group of diseases caused by excess uric acid and/or decreased uric acid excretion by the kidneys, and it is a type of metabolic syndrome [ 1 ]. Hyperuricemia is diagnosed if the blood uric acid is higher than 420 μmol/l (7 mg/dl) in males and higher than 357 μmol/l (6 mg/dl) in premenopausal women [ 2 , 3 ]. Many studies have shown that hyperuricemia is the pathological basis of gouty arthritis, kidney stones, renal failure, and metabolic syndromes such as hypertension, atherosclerosis, coronary heart disease, glycolipid metabolic disorders, obesity, and insulin resistance disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%